2020
DOI: 10.2139/ssrn.3676264
|View full text |Cite
|
Sign up to set email alerts
|

Economic Consequences of High Public Debt: Evidence from Three Large Scale DSGE Models

Abstract: and the members of the ESCB Working Group on Public Finance for their useful comments and suggestions. We are also grateful to an anonymous referee for very useful comments and suggestions on the ECB working paper. Any remaining errors are ours. The views expressed in this paper are those of the authors and do not necessarily reflect those of the European Central Bank or the ESCB Working Group on Public Finance and its members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
(75 reference statements)
1
18
0
1
Order By: Relevance
“…Our findings support the social causation hypothesis [ 24 ] by showing that both lower individual income as well as a generally increased federal government debt contributed to increased psychological distress over 12 months of the pandemic in Germany. This is also consistent with some previous studies suggesting that high government debt can hamper growth, and that countries with high government debt are vulnerable to adverse shocks [ 16 , 22 , 34 ]. On the other hand, an increase in government debt can stimulate economic growth via the resultant employment generation and through productive investment [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings support the social causation hypothesis [ 24 ] by showing that both lower individual income as well as a generally increased federal government debt contributed to increased psychological distress over 12 months of the pandemic in Germany. This is also consistent with some previous studies suggesting that high government debt can hamper growth, and that countries with high government debt are vulnerable to adverse shocks [ 16 , 22 , 34 ]. On the other hand, an increase in government debt can stimulate economic growth via the resultant employment generation and through productive investment [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, rising government debt is a good way to obtain extra funds to invest in economic growth and productive employment in the short run [ 21 ]. On the other hand, unsustainable government debt accrued during the COVID-19 pandemic may raise interest rates and lower national income, which can lead to a fiscal crisis in the medium/long run [ 22 ]. In addition to debt, one study explored the initial impact of the pandemic on economic wellbeing, and found that about 20% of respondents were financially fragile [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first (Eurostat, 2020b). As stipulated by the European Central Bank, countries with high levels of public debt are more vulnerable to the economic consequences of a crisis (Burriel, Checherita-Westphal, Jacquinot, Schon, & Staḧler, 2020).…”
Section: Preparedness For the Pandemicmentioning
confidence: 99%
“…High indebtedness can affect output on long-term, due to the rise in sovereign spreads and sovereign yields, financial intermediation and increase in future distortionary taxation (Burriel et al, 2020).…”
Section: Theoretical Considerations Regarding Economic Growth and Public Debt Sustainabilitymentioning
confidence: 99%